The complex regional effects of macro-institutional shocks: Evidence from EU economic integration over three decades - Timo Mitze; Philipp Breidenbach (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
We use four subsequent EU enlargement waves over three decades (1980s, 1990s, 2000s) to assess the regional effects of macro-institutional changes. Our focus is set on EU internal border regions which are specifically exposed to international integration, but it remains unclear how they benefit from this exposure. Treatment effects for different outcomes (per capita GDP, labor productivity, employment, population, night light emissions) are estimated by comparing the performance of EU internal border regions to overall regional development trends in the EU. We find significant border effects that build up over time and decay with spatial distance to the enlargement border. While per capita GDP, labor productivity levels and night light emissions develop positively on average, negative effects are found for the employment rate in border regions. However, effects can be specific to enlargement waves and country groups considered: Border regions in established member countries mainly gain from EU enlargement in terms of increasing their GDP per capita and labor productivity levels but face lower employment rates and population decline. However, border regions in new member countries, particularly in 2004 and 2007, most significantly gain through population and employment increases. This complex pattern of effects makes a straight 'winner-loser' categorization difficult and poses challenges to policy support for EU border regions. – – Wir nutzen die vier Erweiterungswellen der EU aus den 1980er, 1990er und 2000er, um die regionalen Auswirkungen dieser Erweiterungen auf die Grenzregionen an den betroffenen Binnengrenzen zu untersuchen. Diese EU-Grenzregionen, die durch die Erweiterung in das Zentrum der EU rücken, erfahren die Effekte der wirtschaftlichen Integration in besonderem Maße, wobei vorab unklar bleibt, wie sich diese auswirken. Wir untersuchen die Effekte auf verschiedene Kennziffern: Pro-Kopf-BIP, Arbeitsproduktivität, Beschäftigung, Bevölkerung, nächtliche Lichtemissionen. Wir finden signifikante Grenzeffekte, die sich im Laufe der Zeit aufbauen und mit der räumlichen Entfernung zur Erweiterungsgrenze abnehmen. Während sich das Pro-Kopf-BIP, das Niveau der Arbeitsproduktivität und die nächtlichen Lichtemissionen im Durchschnitt positiv entwickeln, finden wir negative Effekte für die Beschäftigungsquote. Die Effekte sind jedoch spezifisch für die betrachteten Erweiterungswellen und Ländergruppen: Grenzregionen in etablierten Mitgliedsländern profitieren vor allem durch eine Steigerung des Pro-Kopf-BIP und der Arbeitsproduktivität, erfahren aber niedrigere Beschäftigungsquoten und einen Bevölkerungsrückgang. Die Grenzregionen in den neuen Mitgliedsländern profitieren hingegen am stärksten durch Bevölkerungs- und Beschäftigungszuwächse, insbesondere in den Jahren 2004 und 2007. Dieses komplexe Muster von Effekten macht eine eindeutige "Gewinner-Verlierer"-Kategorisierung schwierig und stellt eine Herausforderung für die politische Unterstützung der EU-Grenzregionen.
Keywords: C23; F15; O47; R11; 330; Economic integration; EU enlargement; internal border regions; regional development; treatment effect estimation